Molecular dynamics simulations of diamond-like carbon overcoat - Khaw, Kok Liang (2015)
In this project, the effect of density on hardness of diamond-like carbon (DLC) thin film was studied by using molecular dynamics (MD) simulation. Three amorphous carbon samples with densities of 2.6 g/cm3, 2.9 g/cm3, and 3.2 g/cm3 were generated using the adaptive intermolecular reactive bond order (AIREBO) potential. The analysis of radial distribution function (RDF) graph shows that the 3.2 g/cm3 amorphous carbon sample has the highest sp3 content of 48.7%, while the 2.9 g/cm3 and 2.6 g/cm3 samples contain 16.5% and 8.0% of sp3 bond respectively. These samples were then subjected to nanoscratching at 10% and 20% penetration depth which correspond to 0.4 nm and 0.8 nm respectively. The load acting on the scratch tip was computed and recorded every 1000 steps during the simulation. Results obtained suggest that sample with higher density possesses higher hardness, hence require higher scratching force.